Plume dynamics in nanosecond and femtosecond laser ablation of metal - Donnelly, Tony (Trinity College (Dublin, Ireland). School of Physics, 2010)
This thesis examines the ablation plume produced from nanosecond and femtosecond laser ablation of metal targets in vacuum. Optical emission and absorption spectroscopy, a time-of-flight Langmuir ion probe and ablation depth measurements were used to study the ablation process. Nanosecond laser ablation plasma was also investigated as a deposition source for metal nanostructured film fabrication.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.